Determinar que existe la desigualdad de género mediante un análisis jurídico al Artículo 110 Numeral 6 del Código Civil Ecuatoriano - Villegas Barros, Mercedes Libertad (2015)
Gender equality is a constitutional principle which states that men and women are equal before the law, which means that everyone, without distinction whatsoever have the same rights and duties towards the state and society as a whole. We know that is not enough to enact equality in law if in reality it is not a fact. So that it is, equality must be translated into real and effective opportunities to go to school, equality before the law, access to work, to health care and social security; compete for jobs or elected positions; enjoy freedom to choose partner, form a family and participate in the affairs of our communities, organizations and political parties. In the art. 23, paragraph 3; it hints at equality before the law, where it is expressed "... all persons shall be considered equal and enjoy the same rights, freedoms and opportunities without discrimination on grounds of birth, age, sex, ethnicity, language, religion ... " As is the feeling of science and spirit of the Constitution, is nothing other than the right to have no exceptions or privileges which do not exclude some of what is given to others in similar circumstances are established. Equality implies uniformity and fairness, which links it with the principle of generality of law. The thought of equality occurs intimately arranged with justice, in a sense be said to be treated fairly is equivalent to being treated in equal ways. From these considerations it is considered after a law firm to article Article 110 Paragraph 6 of the Ecuadorian Civil Code in which it has become clear discrimination against women, in can be seen that the legislator sees only responsible to women but not to man. Through this conceptual study compared deficiency legal doctrine and legal delays the Civil Code was evident, violating rights and equality between man and woman